Predictive value of creatinine-cystatin C ratio for mortality and technique failure in anuric peritoneal dialysis patients - Zhihong Zhang; Tingting Zhou; Man Zhang; Shuiqin Cheng (Renal Failure)
Objectives Both serum creatinine and cystatin C serve as dependable markers of renal function and have demonstrated a correlation with clinical outcomes in diverse conditions, particularly through the ratio of creatinine to cystatin C (Cr/CysC). Anuric patients undergoing peritoneal dialysis (PD) depend entirely on the clearance of peritoneal solutes. This research posits that the Cr/CysC ratio may predict all-cause mortality and technique failure in anuric PD patients.Methods A cohort of 224 anuric PD patients was recruited from January 1, 2014, to December 31, 2019, with follow-up extending until December 31, 2023. The Cr/CysC ratio was computed by dividing the serum creatinine concentration by the cystatin C concentration obtained on the same day. We evaluated the relationship between the Cr/CysC ratio and patient survival, as well as technique failure, utilizing Cox regression and competing risk analyses.Results The average age of the participants was 50.46 ± 12.63 years, with 99 individuals (44.2%) being male. Among all subjects, the Cr/CysC ratio was found to be 1.85 ± 0.56. After controlling for potential confounders, Cox proportional hazards models revealed that the Cr/CysC ratio was significantly linked to the risk of all-cause mortality and technique failure (HR = 0.330, 95% CI 0.124-0.881, p = 0.027; HR = 0.440, 95% CI 0.267-0.726, p = 0.002). Importantly, the significant associations observed in the Cox regression analysis persisted even after accounting for competing risks.Conclusion The Cr/CysC ratio at baseline was recognized as an independent predictor of all-cause mortality and technique failure in anuric PD patients.